Pharmacovigilance in hospice/palliative care: net effect of haloperidol for nausea or vomiting - Digges, Madeline; Hussein, Akram; Wilcock, Andrew; Crawford, Gregory B.; Boland, Jason W.; Agar, Meera R.; Sinnarajah, Aynharan; Currow, David C.; Johnson, Miriam J. (Mary Ann Liebert, 2018)
Background: Haloperidol is widely prescribed as an antiemetic in patients receiving palliative care, but there is limited evidence to support and refine its use.